A ZnS/CaZnOS Heterojunction for Efficient Mechanical-to-Optical Energy Conversion by Conduction Band Offset - Peng, Dengfeng (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2020 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.